Direct preparation of efficient catalyst for oxygen evolution reaction and high-purity Li2CO3 from spent LiNi0.5Mn0.3Co0.2O2 batteries. (1st November 2019) - Yang, Yongxia; Yang, Hailun; Cao, Hongbin; Wang, Zhonghang; Liu, Chunwei; Sun, Yong; Zhao, He; Zhang, Yi; Sun, Zhi
Abstract: The recovery of waste lithium-ion batteries (LIBs) is an intensively studied worldwide because of environmental pollution and the risk of undersupply of a strategic raw material. Traditional technologies have poor selectivity for lithium recovery from waste LIBs. Metallic Ni, Co, and Mn are usually recovered by leaching, precipitation, and solvent extraction. These recycling methods are costly and have a long recycling route and high potential for secondary waste generation. In this paper, a mechanochemical activation approach was proposed for the selective recycling of lithium and recovery of Ni0.5 Mn0.3 Co0.2 (OH)2 from spent LiNi0.5 Mn0.3 Co0.2 O2 batteries. The leaching efficiency and Li selectivity were found to be 95.10% and 100%, respectively. The structure of Ni0.5 Mn0.3 Co0.2 (OH)2 was investigated using various characterisation techniques. The selective reaction mechanism of mechanochemical activation was identified. High-purity Li2 CO3 (99.96 wt%) was obtained. Electrochemical tests showed that the performance of Ni0.5 Mn0.3 Co0.2 (OH)2 was comparable to that of a commercial oxygen evolution reaction catalyst (IrO2 ). This research demonstrates an effective and shorter route from waste to a functional material during recycling spent LIBs that incorporates the principles of green chemistry and shows great potential for practical application. Graphical abstract: Image 1 Highlights: The high leaching efficiency and selectivity of Li are obtained using. Mechanochemical reaction. The selective reaction mechanism of mechanochemical activation is identified. The high-purity Li2 CO3 is recovered. The recovered Ni0.5 Mn0.3 Co0.2 (OH)2 exhibits high OER activity.